Someone to count on: social support as an effect modifier of viral load suppression in a prospective cohort study. Issue 4 (3rd April 2017) - Friedman, M. Reuel; Coulter, Robert W.S.; Silvestre, Anthony J.; Stall, Ron; Teplin, Linda; Shoptaw, Steve; Surkan, Pamela J.; Plankey, Michael W.
ABSTRACT: Though functional social support has been shown to serve as a protective factor for HIV viral load suppression in other populations, scant research has examined this relationship among men who have sex with men (MSM) in the United States. We assessed characteristics of social support, effects of social support on HIV viral load, and moderation by social support of the relationship between psychosocial indicators of a synergistic epidemic (syndemic) and HIV viral load. We analyzed longitudinal data from HIV-positive MSM using antiretroviral therapy who were enrolled in the Multicenter AIDS Cohort Study between 2002 and 2009 ( n = 712). First, we conducted reliability assessments of a one-item social support measure. Then, we conducted a series of generalized longitudinal mixed models to assess our research questions. Moderation was assessed using an interaction term. A three-level (low/medium/high) social support variable demonstrated high reliability (intraclass correlation coefficients = 0.72; 95% CI: 0.70, 0.75). Black and Hispanic MSM reported lower social support than their White counterparts ( p < .0001). Recent sero-conversion was associated with higher social support ( p < .05). Higher numbers of concomitant syndemic indicators (depression, polysubstance use, and condomless anal sex) were associated with lower social support ( p < .0001). Medium and high social support levels were associated with greater viral load suppression and lower viral load means ( p < .0001). Social support moderated the relationships between syndemic and HIV viral load ( p < .05). HIV-positive MSM, particularly those of color, may benefit greatly from interventions that can successfully boost functional social support. Creating strengths-based interventions may also have particularly high impact among HIV-positive MSM with the highest psychosocial burdens.